Longitudinal mood monitoring in bipolar disorder: Course of illness as revealed through a short messaging service. - McKnight, RF; Bilderbeck, AC; Miklowitz, DJ; Hinds, C; Goodwin, GM; Geddes, JR (Elsevier, 2017)
Background Online self-monitoring of mood can be used to investigate differences in course patterns across patient groups. This study explored the feasibility of remote symptom capture with True Colours, a self-rated online mood monitoring tool completed on a weekly basis. Methods Participants with bipolar disorder (N = 297) completed weekly depression and mania questionnaires over an average of 27.5 months (range 1 –81 months). Subgroups defined by sex, age, and bipolar I vs. II status were compared on time in various mood states, number of episodes, and week-to-week mood variability. Results Compliance with weekly questionnaires was generally high (median, 92% of weeks). Mood symptoms occurred for an average of 55.4% of weeks across the follow-up period. Females spent more time with hypomanic/manic and depressive symptoms and had more depressive episodes compared to males. Younger participants were found to experience more hypomanic/manic episodes and showed greater variability in mood symptoms than older participants. No significant differences in mood symptoms or variability were observed between bipolar I and II patients. Limnitations This was a naturalistic study with a heterogeneous cohort, and did not include a control group. True Colours does not identify mood fluctuations that may occur in the days between weekly assessments. Conclusions Monitoring moods through an online tool is both feasible and informative regarding course of illness in patients with bipolar disorder. Interventions aiming to reduce mood variability and manic/hypomanic episodes in the early phases of bipolar disorder may enhance the long-term symptomatic course of the illness.